Prenatal diagnosis of caudal regression syndrome in a non-diabetic mother: a rare case report - Kumar, Mukesh; Iqbali, Tauhid; Bassi, Harish; Singh, Harpreet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Caudal regression syndrome (CRS) is a rare congenital malformation characterized by partial or complete agenesis of the sacrum and variable involvement of lumbar spine and lower limbs. It is classically associated with maternal diabetes, though sporadic cases in non-diabetic mothers have been reported. We report a case of a 25-year-old gravida 2 para 1 live 1 woman with previous lower segment caesarean section (LSCS) three years back, non-diabetic, who was diagnosed prenatally at 20 weeks of gestation with CRS on level II ultrasonography. There was a significant family history of type 2 diabetes mellitus in the patient’s mother, along with a history of three intrauterine fetal deaths (IUFDs). The fetus showed abrupt termination of the spine at the lumbosacral level with an absent sacrum and hypoplastic lower limbs. This case highlights that CRS can occur even in the absence of maternal diabetes, emphasizing the importance of detailed anomaly scanning and consideration of genetic and familial factors.